Art 2071 The Moderating Role Of Self-Control In The Relationship Between Sharia Financial Literacy and Paylater Usage Decisions (A Case STUDY Of Uniga Students) - Fitri Syakinah; Resmi Afifah Fadilah; Lina Nurlaela (Al Mashaadir : Jurnal Ilmu Syariah, 2026)
The rapid growth of Buy Now Pay Later (BNPL) services has transformed student consumption patterns but raised risks of consumer debt and usury, often leading to an intention-behavior gap where high religious knowledge fails to curb digital debt behavior. This study aims to investigate the influence of Sharia Financial Literacy on Paylater Usage Decisions among Accounting and Management students at Garut University, with Self-Control serving as a moderating variable. Employing a quantitative associative approach with a cross-sectional survey method, data were collected via digital questionnaires alongside qualitative micro-focus group discussions for instrument validation. The sample consisted of 100 active students selected through purposive sampling, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The structural model evaluation shows that Sharia Financial Literacy does not have a significant influence on students' paylater usage decisions (p = 0.129), indicating that theological understanding is often secondary to practical considerations. Conversely, Self-Control has a positive and significant direct effect on usage decisions (p = 0.000), showing that students with strong self-control do not avoid paylater but utilize it in a planned, measured, and responsible manner to manage short-term cash flow. Furthermore, Self-Control does not act as a moderating variable in the relationship between Sharia Financial Literacy and paylater decisions (p = 0.413), as both factors operate independently. In conclusion, individual financial decisions in the fintech ecosystem are heavily driven by psychological behavioral discipline rather than normative religious literacy or its interactive combination.